AKTIVITAS INSEKTISIDA EKSTRAK BIJI TRICHILIA TRIJUGA ROXB. (MELIACEAE) TERHADAP ULAT DAUN MELATI PALPITA UNIONALIS (HÃœBNER) - Ika Sartika , Djoko Prijono Gustini Syahbirin , dan Maryam Abn. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2001)
Insecticidal activity of Trichilia trijuga Roxb. (Meliaceae) seed extracts against jasmine leaf caterpillar Palpita unionalis (Hübner). The insecticidal activity of Trichilia trijuga seed extracts was evaluated in the laboratory against the jasmine leaf caterpillar Palpita unionalis. Acetone neem (Azadirachta indica) seed extract and NeemAzal T/S formulation (a.i.: 1% azadirachtin) were included in the test as positive controls. First-instar larvae of P. unionalis were fed with treated jasmine leaves for 2 days, then surviving larvae were fed with untreated leaves and observed daily until reaching third-instar stage. The treatments with acetone extract and aqueous extract of T. trijuga at concentrations of 0.175% and 21 g of seeds/l of water (2.1%), respectively, caused a complete kill in the test larvae. The insecticidal activity of T. trijuga acetone extract at 0.175% was comparable with that of NeemAzal preparation containing azadirachtin of about 10 – 17.5 ppm. Based on larval mortality until the third instar, LC50 of acetone extract and aqueous extract of T. trijuga were 0.024% and 0.307%, respectively (LC50 of acetone neem seed extract was 0.018%). In addition to lethal effect, T. trijuga seed extracts also delayed the development of the surviving larvae; for example, the treatment with T. trijuga acetone extract at 0.1% prolonged the developmental time of P. unionalis larvae to the third instar by 3 days compared to control. It is concluded that T. trijuga seeds serve as a potential source of botanical insecticides, particularly against P. unionalis.